Interrogating Datafication Towards a Praxeology of Data - Burkhardt, Marcus; van Geenen, Daniela; Gerlitz, Carolin; Hind, Sam; Kaerlein, Timo; Lämmerhirt, Danny; Volmar, Axel (Media in Action, 2022)
What constitutes a data practice and how do contemporary digital media technologies reconfigure our understanding of practices in general? Autonomously acting media, distributed digital infrastructures, and sensor-based media environments challenge the conditions of accounting for data practices both theoretically and empirically. Which forms of cooperation are constituted in and by data practices? And how are human and nonhuman agencies distributed and interrelated in data-saturated environments? The volume collects theoretical, empirical, and historiographical contributions from a range of international scholars to shed light on the current shift from media to data practices.